PENERAPAN SAK EMKM PADA PENCATATAN LAPORAN KEUANGAN SEDERHANA UMKM DI KULON PROGO - Isdyantanti, Nisa; Zaenal Wafa (Politeknik Negeri Sriwijaya, 2023)
The application of SAK EMKM in assisting the recording of simple financial reports for MSMEs in Kulon Progo aims to help MSME players to increase their insight and training in preparing financial reports. Financial reports have a role in MSMEs to provide business information, financial conditions and develop their businesses. The SAK EMKM Financial Report includes; profit and loss report, capital changes report and notes to financial statements. Activities are carried out using direct training methods through Excel accounting and financial report form output.